The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2054270417718712
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral arthrodesis of the distal tibiofibular joint for deforming osteochondromatas

Abstract: LessonThe first case of bilateral distal tibiofibular joint fusions for osteochondromas is reported with excellent long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Among those patients, 4 achieved a full ROM of the ankle joint without pain at 1 year after surgery. Ribbans et al 19 demonstrated that distal tibiofibular fusions were rare, with the following indications being the most common: salvage following syndesmotic injury with a chronic, symptomatic diastasis following Weber B and C and ankle fractures or, more rarely, isolated chronic syndesmotic injuries with instability. Miyamoto and Takao 13 recommended arthrodesis of the distal tibiofibular joint for chronic cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those patients, 4 achieved a full ROM of the ankle joint without pain at 1 year after surgery. Ribbans et al 19 demonstrated that distal tibiofibular fusions were rare, with the following indications being the most common: salvage following syndesmotic injury with a chronic, symptomatic diastasis following Weber B and C and ankle fractures or, more rarely, isolated chronic syndesmotic injuries with instability. Miyamoto and Takao 13 recommended arthrodesis of the distal tibiofibular joint for chronic cases.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 24 Despite the fact that many surgical techniques have been described in the literature, little evidence is available with regard to the indications, procedures, and outcomes of fusion techniques or how to manage with combined disorders. 19 As for postoperative rehabilitation protocol, it remains controversial that if it should be related to screw removal decision: some authors advocate removal of the screws before weightbearing, 1 , 4 while others suggest no significant difference in outcome between the retained and removed screws. 8 , 16 On the other hand, chronic syndesmosis injury presents a significant challenge for athletes especially, where early return to sport is of great importance.…”
mentioning
confidence: 99%